THE USE OF GAMIFICATION IN THE PREVENTION OF DYSLEXIA OF CHILDREN IN PRESCHOOL AGE - Hanna Mytsyk; Alona Babichenko (Інформаційні технології і засоби навчання)
In this article, the use of gamification in the organization of preventive work with children prone to dyslexia is analyzed. The factor that causes dyslexia has been identified, emphasizing the need to promptly identify children at risk and intervene, in order to avoid negative psychosocial consequences during their education. The main achievements of scientists in this field have been summarized. The advantages of using individual elements of gamification for propaedeutic purposes in working with children prone to dyslexia are highlighted, and their description is provided. An algorithm for creating a game mechanism, criteria for selecting digital learning platforms, and developing games based on them are proposed.